2014
DOI: 10.1177/1535370214543064
|View full text |Cite
|
Sign up to set email alerts
|

The diabetic rat kidney mediates inosituria and selective urinary partitioning of D-chiro-inositol

Abstract: Diabetic nephropathy is a serious complication of diabetes mellitus with a pressing need for effective metabolic markers to detect renal impairment. Of potential significance are the inositol compounds, myo-inositol (MI), and the less abundant stereoisomer, D-chiro-inositol (DCI), which are excreted at increased levels in the urine in diabetes mellitus, a phenomenon known as inosituria. There is also a selective urinary excretion of DCI compared to MI. As the biological origins of altered inositol metabolism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
2
14
0
1
Order By: Relevance
“…Indeed, a study of Chang et al ( 26 ) on isolated kidneys has shown that perfusion conditions replicating hyperglycaemia (20 m m -glucose) significantly potentiated D -chiro-inositol (DCI) but not MI urinary excretion in both non-diabetic and diabetic kidneys. The diabetic kidneys, however, presented 2-fold increased urinary excretion of myo -inositol compared with the non-diabetic kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a study of Chang et al ( 26 ) on isolated kidneys has shown that perfusion conditions replicating hyperglycaemia (20 m m -glucose) significantly potentiated D -chiro-inositol (DCI) but not MI urinary excretion in both non-diabetic and diabetic kidneys. The diabetic kidneys, however, presented 2-fold increased urinary excretion of myo -inositol compared with the non-diabetic kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…[113] Compared with the kidneys from nondiabetic rats,those from diabetic rats had af ourfold greater excretion of d-chiroinositol under normoglycemic conditions,w ith higher excretion under hyperglycemic conditions. [114] Increases in myoinositol excretion also occurred but were not as great, despite increased renal expression of both SMIT1 and SMIT2.…”
Section: Angewandte Chemiementioning
confidence: 97%
“…It is noticeable that, despite increased expression of the inositol transporter systems (SMT1/2), inositol reabsorption is significantly inhibited at the tubular level [ 136 ]. Other pathophysiological processes should therefore explain increased urinary loss of inositol isomers in diabetic kidneys [ 137 ].…”
Section: Inositol Deficiencymentioning
confidence: 99%